Perencanaan Peningkatan Kualitas Produk Raket dengan Metode Quality Function Deployment - Lukman, Moh. (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
Small Industry Abadi location in central small industry raket Sukun-Malang, so many kinds racket product are many variables as, racket quality, raket colors, rakets price, will give the customer many choice product rackets. Demand racket products are fluctuative from periods to another periods because there are factors: school holiday, and badminton championship in scale national cup and world cup as All England so demand will be increase. In central small industry raket thre are many small industry racket, so competition raket product increase,so there are the price will be cheap and quality may be too lower. This competition cause qoitition in raket